Industrial Subsidies in the OECD Economies - Ford, Robert (OECD Economics Department Working Papers, 1990)
Subsidisation of industrial activities distorts the allocation of scarce resources, is a burden on government finances and generates friction in international trade. This paper draws on a wide range of data sources to examine industrial subsidisation in OECD countries. The sectoral distribution of subsidies and the relative importance of the different instruments of subsidisation are highlighted. The final section of the paper evaluates, to the extent possible, the economic effects of subsidy policy ...